Portfolio of socio-technical innovations in low- emission food systems in Caquetá, Colombia - Clavijo, Neidy; Rodríguez, Luz A; Vanegas, Martha (2024)
The Amazon rainforest, covering 40% of Colombia’s territory, is a vital source of ecosystem services but faces significant deforestation driven by agro-industrial crops and extensive livestock farming, with over 60% of the country’s deforestation occurring in the region. This deforestation is exacerbated by unsustainable practices that increase greenhouse gas (GHG) emissions and degrade soil, water, and biodiversity. To address these challenges, sociotechnical innovations that mimic the Amazon's natural ecosystems, such as agroforestry, silvopastoral systems, and agroecological practices, are crucial for reducing emissions and improving sustainability. This report focuses on sociotechnical innovations in Caquetá, Colombia, through a literature review and field interviews, highlighting both current practices and areas for improvement. Key innovations identified include biodigesters, alternative market systems, and participatory guarantee schemes. Although local producers have adopted agroforestry and organic production, there is potential to further develop these practices through innovation labs, ensuring better alignment with the region’s socioecological needs.